Extended use of gamma irradiation in wild mushrooms conservation: validation of 2 kGy dose to preserve their chemical characteristics - Fernandes, Ângela (2016)
Irradiation is recognized by international organizations as a conservation technology, and its application to wild mushrooms has been tested in some species. Our research group evaluated the effectiveness of gamma irradiation to conserve different samples of highly appreciated species, particularly, Lactarius deliciosus, Macrolepiota procera, Boletus edulis and Hydnum repandum. From those results and considering also international recommendations on this subject, the 2 kGy dose was chosen for further studies. Therefore, the application of gamma irradiation at 2 kGy dose was extended to Boletus pinophilus Pilát & Dermek and Clitocybe subconnexa Murrill to validate the proposed technology. Considering the obtained results, some of the analysed chemical parameters (specially sugars and fatty acids), as well as the antioxidant activity, showed significant changes after irradiation treatment, particularly in B. pinophillus, probably due to its higher water content. Nevertheless, the obtained differences did not seem to be sufficient to change the organoleptic characteristics of these mushrooms. Furthermore, the antioxidant activity was generally higher in irradiated samples. In conclusion, the detected chemical changes might be considered as acceptable, when considering the high advantages of gamma irradiation at decontamination and/or disinfestation level.